Neoliberalismo como forma de subjetivación dominante (2017)
ABSTRACT: In this paper, the authors approach the issue of new forms of subjectivation promoted by neoliberalism. We start from the Foucaultian conception of power as governance, understood as the leading of the behavior of others. To achieve this, we establish the ruptures and discontinuities between the liberal and neoliberal government rationalities as well as the effects this has had on the shaping of subjectivities. We conclude that, in contemporary times, emerging subjectivity occurs in self-entrepreneurs. Furthermore, we state that these individuals: (1) behave as entrepreneurs; (2) turn their own lives into human capital that must be increased through investments on oneself so that the self-company obtains better performance; (3) build new ways of establishing bonds based on the market, and (4) are governed under the promise of absolute freedom, the cult of risk and the discourse of flexibility.